A microwave-assisted and environmentally benign approach to the synthesis of near-infrared fluorescent pentamethine cyanine dyes. (February 2015) - Owens, Eric A.; Bruschi, Nicholas; Tawney, Joseph G.; Henary, Maged
Abstract: A time-efficient and eco-conscious microwave methodology was developed and applied to synthesize a systematic library of pentamethine cyanine dyes and their corresponding precursors. The synthesis outlined herein drastically reduced the reaction pathway for pentamethine carbocyanine dye syntheses from days to min, as well as producing increased yields (89–98%) to the conventional heating method (18–64%). Twelve examples of pentamethine cyanine dyes were synthesized by means of microwave-assisted organic synthesis which provided excellent yield in expedited reaction time and were obtained using facile isolation methods. Furthermore, three cyanines were prepared with a novel methylene dioxy heterocyclic structure which imparted an approximately 40 nm bathochromic shift compared to unsubstituted counterparts; these results were shown to be in agreement with DFT calculations and HOMO-LUMO energy differences. Graphical abstract: Highlights: The synthesis of pentamethine cyanines was developed using eco-friendly methods. Dipole moment calculations helped determine optimum microwave reaction temperature. Three compounds feature red-shifted optical properties arising from a methylene dioxy group. HOMO-LUMO energy gaps agree with the observed wavelengths.